Induction chemotherapy (IC) followed by radiotherapy (RT) versus cetuximab plus IC and RT in advanced laryngeal/hypopharyngeal cancer resectable only by total laryngectomy—final results of the larynx organ preservation trial DeLOS-II. (23rd August 2018) - Dietz, A; Wichmann, G; Kuhnt, T; Pfreundner, L; Hagen, R; Scheich, M; Kölbl, O; Hautmann, M G; Strutz, J; Schreiber, F; Bockmühl, U; Schilling, V; et al.
Abstract: Background: The German multicenter randomized phase II larynx organ preservation (LOP) trial DeLOS-II was carried out to prove the hypothesis that cetuximab (E) added to induction chemotherapy (IC) and radiotherapy improves laryngectomy-free survival (LFS; survival with preserved larynx) in locally advanced laryngeal/hypopharyngeal cancer (LHSCC). Patients and methods: Treatment-naïve patients with stage III/IV LHSCC amenable to total laryngectomy (TL) were randomized to three cycles IC with TPF [docetaxel (T) and cisplatin (P) 75 mg/m 2 /day 1, 5-FU (F) 750 mg/m 2 /day days 1–5] followed by radiotherapy (69.6 Gy) without (A) or with (B) standard dose cetuximab for 16 weeks throughout IC and radiotherapy (TPFE). Response to first IC-cycle (IC-1) with ≥30% endoscopically estimated tumor surface shrinkage (ETSS) was used to define early responders; early salvage TL was recommended to non-responders. The primary objective was 24 months LFS above 35% in arm B. Results: Of 180 patients randomized (July 2007 to September 2012), 173 fulfilled eligibility criteria (A/B: larynx 44/42, hypopharynx 41/46). Because of 4 therapy-related deaths among the first 64 randomized patients, 5-FU was omitted from IC in the subsequent 112 patients reducing further fatal toxicities. Thus, IC was TPF in 61 patients and TP in 112 patients, respectively. The primary objective (24 months LFS above 35%) was equally met by arms A (40/85, 47.1%) as well as B (41/88, 46.6%). One hundred and twenty-three early responders completed IC+RT; their overall response rates (TPF/TP) were 94.7%/87.2% in A versus 80%/86.0% in B. The 24 months overall survival (OS) rates were 68.2% and 69.3%. Conclusions: Despite being accompanied by an elevated frequency in adverse events, the IC with TPF/TP plus cetuximab was feasible but showed no superiority to IC with TPF/TP regarding LFS and OS at 24 months. Both early response and 24 months LFS compare very well to previous LOP trials and recommend effective treatment selection and stratification by ETSS. Clinical trial information: NCT00508664.